1994
DOI: 10.1002/bit.260430406
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant pretreatment of a polysulfone ultrafilter for reduction of antifoam fouling

Abstract: Effectiveness of surfactant precoat treatment of the polysulfone ultrafilter was first investigated for reduction of membrane fouling in ultrafiltration of antifoam. Fifteen different surfactants, including alcohols and synthetic nonionic surfactants, were tested. In general, pretreatment with nonionic surfactant gave a larger flux than that with alcohol did. The flux increase by pretreatment with nonionic surfactant depended on a hydrophile lipophile balance (HLB) value and type of hydrophobic tail. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Pretreatment of the CA and PA membranes for 1 h with surfactants prior to cell addition frequently resulted in stimulation of bacterial attachment, suggesting modification of the membrane surfaces by certain surfactants. Similar surface modification of polysulfone ultrafiltration membranes was reported by Yamagiwa et al (1994). A group of three selected surfactants that stimulated attachment in the membrane pretreatment assay resulted in inhibition of mycobacteria attachment in the cell pretreatment assay in the CA membrane system, suggesting the cell surface is a primary target for detergent activity.…”
Section: Discussionsupporting
confidence: 73%
“…Pretreatment of the CA and PA membranes for 1 h with surfactants prior to cell addition frequently resulted in stimulation of bacterial attachment, suggesting modification of the membrane surfaces by certain surfactants. Similar surface modification of polysulfone ultrafiltration membranes was reported by Yamagiwa et al (1994). A group of three selected surfactants that stimulated attachment in the membrane pretreatment assay resulted in inhibition of mycobacteria attachment in the cell pretreatment assay in the CA membrane system, suggesting the cell surface is a primary target for detergent activity.…”
Section: Discussionsupporting
confidence: 73%
“…According to morphology analysis performed by ESEM (section ), immobilization of TRX/gA does not affect membrane porosity. It has been reported that exposure to the surfactant enhances wetting properties of polymeric membranes and can enhance water uptake properties, which is observed also in the present case.…”
Section: Results and Discussionsupporting
confidence: 82%
“…The influence of Triton X100 (TRX) on the water flux properties of the polymeric membranes has been previously reported, and it was found that treatment with a surfactant significantly enhances water passage through the polymeric membranes. Because the water flux is expected to increase after treatment with Triton solution, overall ion passage is going to increase as well. Because TRX treatment and TRX/gA micelle immobilization imply interaction of the membrane surface with the surfactant, we expect both modifications to improve ion permeability.…”
Section: Results and Discussionmentioning
confidence: 99%